IMPLEMENTASI PASAL 55 UNDANG-UNDANG NOMOR 6 TAHUN 2018 TENTANG KEKARANTINAAN KESEHATAN PADA MASA PANDEMI COVID-19 (STUDI KASUS KOTA BANDAR LAMPUNG) - Sultan Ali Sabana; Baharuddin Baharuddin; Anggalana Anggalana (Fakultas Hukum Universitas Tulang Bawang, 2022)
Health quarantine is an effort to prevent the impact of infectious disease outbreaks that can attack a place, region, even a country, by closing access in and out and limiting the activities or activities of people in the area that is implementing quarantine. For the sake of implementing a proper health quarantine, it is necessary to pay attention to and consider several factors, such as the economic condition of the community, health services, educational services, and working conditions. The implementation of health quarantine is the responsibility of the Government as a manifestation of the State to be able to fulfill all the factors that can support the implementation of health quarantine in an area without causing new problems in people's lives. The government enforces health quarantine with various patterns, such as the implementation of Large-Scale Social Restrictions (PSBB) to the Enforcement of Restrictions on Community Activities (PPKM). As a state of law, Indonesia certainly underlies the implementation of health quarantine by referring to the constitution of the State of Indonesia, namely Law number 6 of 2018 concerning Health Quarantine. The purpose of this study is to analyze the implementation of Article 55 of Law Number 6 of 2018 concerning Health Quarantine in Bandar Lampung City and analyze the fulfillment of citizens' rights in the implementation of Community Activity Restrictions (PPKM) in Bandar Lampung City. The method used in this research is normative juridical and empirical juridical. The data that has been systematically arranged were analyzed qualitatively. In this data analysis process, a series of data that has been systematically arranged according to its classification, is then described and analyzed in a normative and empirical juridical manner, namely the approach taken based on the main legal material by examining theories, concepts, principles and laws and regulations related to this research as well as the results of interviewing parties related to the results of this study. Keywords : health quarantine, Covid-19, PPKM, Government, Peopel